ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA DAN PERTUMBUHAN EKONOMI DI SUMATERA BARAT - Fitri, Irdas; Syofyan, Efrizal; Aimon, Hasdi (Jurnal Kajian Ekonomi, 2015)
This study aimed to analyze the effect of (1) public investment education sector, the health sector and public investment on labor productivity IPM West Sumatra (2) labor productivity, shopping areas, infrastructure and income inequality on economic growth of West Sumatra. This type of research is descriptive and associative. While this type of data is data documentary, source of data is secondary data as well as data in the form of data panel with 19 districts / cities from 2010 - 2013. This study uses a simultaneous equation model analysis tool with Indirect methods Stages Least Squared (ILS). The study concluded that (1) public investment education sector, the health sector and public investment IPM significant effect on labor productivity in West Sumatra. With the meaning of words, if public investment and public investment education sector increased health sector and accompanied by HDI is the better it would be the better labor productivity in the area. (2) shopping areas, infrastructure and income inequality affects economic growth in West Sumatra significantly. That is, the increase in shopping areas, improved infrastructure and declining inequality of income then this condition will lead to an increase in the economic growth. Based on these results the policies suggested the government may need to increase budget allocations for education and health. Good quality education will give a good effect on the mindset and behavior patterns of people of West Sumatra. With the increase in budget for health, the public will have better access to services and to health.